2014
DOI: 10.5037/jomr.2014.5401
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Alveolar Nerve Injury after Mandibular Third Molar Extraction: a Literature Review

Abstract: ObjectivesThe purpose of this study was to systematically review the comprehensive overview of literature data about injury to the inferior alveolar nerve after lower third molar extraction to discover the prevalence of injury, the risk factors, recovery rates, and alternative methods of treatment.Material and MethodsLiterature was selected through a search of PubMed electronic databases. Articles from January 2009 to June 2014 were searched. English language articles with a minimum of 6 months patient follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
107
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 63 publications
4
107
0
11
Order By: Relevance
“…Risk factors for IAN deficit include increased age, unerupted tooth, deep impaction, specific radiographic signs and intraoperative IAN exposure, all of which are relevant to this case. This risk is again further increased if the tooth is fully encased by bone and the root apices extend below the neurovascular bundle; again relevant to this case. Incidence of lingual nerve damage during third molar surgery can be between 0.1–22%.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Risk factors for IAN deficit include increased age, unerupted tooth, deep impaction, specific radiographic signs and intraoperative IAN exposure, all of which are relevant to this case. This risk is again further increased if the tooth is fully encased by bone and the root apices extend below the neurovascular bundle; again relevant to this case. Incidence of lingual nerve damage during third molar surgery can be between 0.1–22%.…”
Section: Discussionmentioning
confidence: 92%
“…Recent literature reviews cite the incidence of IAN injury as 0.35-8.4% following lower third molar extraction. However, 96% of damaged IANs fully recover within 4-8 weeks 12 . Risk factors for IAN deficit include increased age, unerupted tooth, deep impaction, specific radiographic signs and intraoperative IAN exposure 13 , all of which are relevant to this case.…”
Section: Discussionmentioning
confidence: 98%
“…However, in a literature review of prospective studies, it was found that age is linked to IAN and lingual nerve deficits and it was the first etiology even before deep impaction, specific radiographic signs, intra-operative IAN exposure and lingual split technique [36]. For Sarikov and Juodzbalys [37] more risks for subjects older than 24 years. Probably, other anatomic and physiologic factors could be involved in having these clinical findings.…”
Section: Discussionmentioning
confidence: 99%
“…1 Due to the close anatomic relation between lower third molars and mandibular canal, odontectomy of impacted lower third molars carry potential risk for injury of inferior alveolar nerve. 2 Injury of inferior alveolar nerve may be due to trauma, inflammation or infection in the periphery of the nerve manifesting clinically as reduced sensation, or paraesthesia, of lower lip and chin of the affected sides.…”
Section: Introductionmentioning
confidence: 99%